Food insecurity amongst asylum seekers and people without status in Israel - Moran Blaychfeld-Magnazi; Zohar Mor; Gaya Sartena; Rebecca Anne Goldsmith; Einat Ophir; Ronit Endevelt (BMC, 2024)
Abstract Background The COVID-19 pandemic caused massive disruptions globally, with food insecurity a primary concern amongst vulnerable communities. As one of the most marginalized and vulnerable groups in Israeli society asylum seekers and undocumented populations were amongst the first to be affected by the pandemic and the economic crisis that followed. The objective of the study was to evaluate the severity and causes of food insecurity among asylum seekers and other undocumented communities because of COVID-19. Methods A multi method approach was used. The quantitative component included an online questionnaire regarding access to food, aid and choices, and the 6 item Household Food Security Survey Module (HFSSM) The qualitative component included 4 focus groups and thematic analysis. The study was conducted in November 2020, by the Ministry of Health's Nutrition Division and the Tel Aviv Municipality's foreign community assistance and information center (Mesila). The convenience sample was drawn from the low-income neighborhood population of South Tel Aviv. Logistic regression, multivariate analysis and content analysis, were performed. Results Four hundred eighty-five people completed the quantitative survey, with average age 33.2 ± 5.4 years and 349 (72.0%) experienced food insecurity. In the multivariate analysis, being older (p = 0.04, Odds Ratio OR 1.1, Confidence Interval CI 1.05-1.15) and being single (unmarried) (p = 0.03, OR 2.1, CI 1.2, 3.5) predicted food insecurity. Qualitative findings identified three main themes: children preferring Israeli/ Western foods to traditional foods; financial stresses were compounded; a preference for receiving assistance with purchasing food (vouchers), rather than food handouts. Conclusion In conclusion, vulnerable populations (asylum seekers and other undocumented communities) were severely affected and are in danger of food insecurity. Culturally relevant and contextualized solutions are needed to address the acute hunger within the community. These include establishment of a cross-ministerial forum, a social grocery store, increased liaison with food rescue bodies, complete nutritional support for children in educational settings and increased guidance regarding food choices and budgeting.